PENGARUH LKPD BERBASIS ETNOMATEMATIKA MOTIF BATIK BESEMAH PADA MATERI TRANSFORMASI GEOMETRI TERHADAP PEMAHAMAN KONSEP SISWA KELAS X DI SMA MUHAMMADIYAH PAGAR ALAM TAHUN PELAJARAN 2025/2026 - Niken Framisi; Novi Susanti; Reza Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using student worksheets based on ethnomathematics of the Besemah batik motif on geometric transformation material on the conceptual understanding of grade X students at Muhammadiyah Pagar Alam High School in the 2025/2026 Academic Year. This study used an experimental method with a pretest-posttest control group design. The study population was all 417 students of class X of Muhammadiyah Senior High School in the 2025/2026 academic year, while the sample was class X.C (Experimental) with 38 students and class X.D (Control) with 38 students. Data collection techniques used documentation and essay-based tests. The average score for the experimental class was 83 and the control class 63. Based on the t-test, the calculated t value was 6.792 > 1.993. Therefore, it can be concluded that learning using ethnomathematics-based worksheets (LKPD) with the Besemah batik motif on geometric transformation material on the conceptual understanding of class X students at Muhammadiyah Senior High School Pagar Alam in the 2025/2026 academic year is better than using conventional learning.